Blockchain : short-term hype or world-changing technology. - Kulikova, Asia; Málek, Jiří, 1953-; Mazáček, David; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
My main goal was to analyse blockchain with all its applications and use cases. Based on this analysis, I wanted to define the vector of its development, biggest challenges, possible threats or alternatively the support from other technologies.Given this, I have also tried to structure my work as a de facto user guide for audience with no previous (or limited knowledge) of blockchain, so that they can gradually develop deeper knowledge and understanding of the problematic. To fulfil this purpose, I divided my thesis into four parts.The first part is devoted to the history of the blockchain development. There I also went through the technical aspects of the technology and the two main platforms based on the market capitalization: Bitcoin and Ethereum. In the second part I have focused at different products of this technology, such as well-known cryptocurrencies. My third chapter revolves around the use cases in the different disrupted fields. Besides the financial services, there are several other sectors, for instance Supply Chain and government. The findings gained in the process of he first three chapters were then applied in the fourth (and final) chapter where I have summarized the challenges and benefits of blockchain and collaboration with other popular technologies today. There I made my practical contribution - a synthesis of all use cases and propose the mechanism of the blockchain society.
Vedoucí práce: Jiří Málek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses